Widespread thiamine deficiency in California salmon linked to an anchovy-dominated marine prey base - Nathan J. Mantua; Heather Bell; Anne E. Todgham; Miles E. Daniels; Jacques Rinchard; Jarrod M. Ludwig; John C. Field; Steven T. Lindley; Freya E. Rowland; Catherine A. Richter; David Walters; Bruce Finney; et al. (Proceedings of the National Academy of Sciences, 2025)
Thiamine (vitamin B 1 ) deficiency in marine systems is a globally significant threat to marine life. In 2020, newly hatched Chinook salmon ( Oncorhynchus tshawytscha ) fry in California’s Central Valley (CCV) hatcheries swam in corkscrew patterns and died at unusually high rates due to a lack of this essential vitamin. We subsequently investigated the impacts and causes of thiamine deficiency in California’s anadromous salmonids. Our laboratory studies defined the relationship between thiamine concentrations in Chinook salmon eggs and early life-stage survival in offspring; we used these data to develop a model that estimated 26 to 48% thiamine-dependent fry mortality across consecutive years (2020–2021) for winter-run Chinook salmon. We established an egg surveillance effort that found widespread thiamine deficiency in CCV Chinook salmon in 2020 and 2021, and emerging thiamine deficiency in Klamath River and Trinity River coho salmon ( Oncorhynchus kisutch ) in 2021. We determined that thiamine injections into adults raised egg thiamine concentrations above levels found to impact early life-stage survival and swimming behavior. Ocean surveys, prey nutrition, salmon gut contents, and stable isotope data link thiamine deficiency to an ocean diet dominated by a booming population of northern anchovy ( Engraulis mordax ). This forage fish had low thiamine, high lipid, and high thiaminase activity levels consistent with both a thiaminase and oxidative stress hypothesis for causing thiamine deficiency in California salmon. Our research suggests California’s already stressed anadromous salmonids will continue to be impacted by thiamine deficiency as long as their ocean forage base and diet are dominated by northern anchovy.